2017
DOI: 10.1101/191221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting temporal dynamics of microenvironmental factors halts tumor migration and alleviates effects of dynamic tumor heterogeneity

Abstract: SummaryTargeting microenvironmental factors that foster migratory cell phenotypes is a promising strategy for halting tumor migration. However, lack of mechanistic understanding of the process impedes pharmaceutical drug development. Using a novel 3D microtumor model with tight control over tumor size, we recapitulated tumor size-induced hypoxic microenvironment and emergence of migratory phenotypes in epithelial T47D breast microtumors as well as those of patient-derived primary metastatic breast cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…Our earlier work has demonstrated that the large 600µm microtumors with tumor-intrinsic hypoxia exhibit partial EMT phenotype characterized by gain of mesenchymal marker (VIM) without loss of epithelial marker (E-CAD) [21]. Based on these initial findings, we further investigated partial EMT signatures enriched by tumor-intrinsic hypoxia in large 600µm microtumors on day 1 and day 6.…”
Section: Large Microtumors Exhibit Enrichment Of Partial Emt Signatur...mentioning
confidence: 90%
See 4 more Smart Citations
“…Our earlier work has demonstrated that the large 600µm microtumors with tumor-intrinsic hypoxia exhibit partial EMT phenotype characterized by gain of mesenchymal marker (VIM) without loss of epithelial marker (E-CAD) [21]. Based on these initial findings, we further investigated partial EMT signatures enriched by tumor-intrinsic hypoxia in large 600µm microtumors on day 1 and day 6.…”
Section: Large Microtumors Exhibit Enrichment Of Partial Emt Signatur...mentioning
confidence: 90%
“…T47D cell line was purchased from American type culture collection (ATCC). Characterization and authentication of T47D cells was done at the University of Arizona Genomic Core facility using PowerPlex16HS PCR kit as previously described [20,21]. All cell culture supplies and media were procured from Corning ® and Mediatech ® , respectively, unless otherwise specified.…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations